Localization of Sir2p: the nucleolus as a compartment for silent information regulators. - Gotta, M (1997)
In wild-type budding yeast strains, the proteins encoded by SIR3, SIR4 and RAP1 co-localize with telomeric DNA in a limited number of foci in interphase nuclei. Immunostaining of Sir2p shows that in addition to a punctate staining that coincides with Rap1 foci, Sir2p localizes to a subdomain of the nucleolus. The presence of Sir2p at both the spacer of the rDNA repeat and at telomeres is confirmed by formaldehyde cross-linking and immunoprecipitation with anti-Sir2p antibodies. In strains lacking Sir4p, Sir3p becomes concentrated in the nucleolus, by a pathway requiring SIR2 and UTH4, a gene that regulates life span in yeast. The unexpected nucleolar localization of Sir2p and Sir3p correlates with observed effects of sir mutations on rDNA stability and yeast longevity, defining a new site of action for silent information regulatory factors.